An Industry Friendly Approach for the Preparation of Magnetic and Electro-Conductive Polyaniline Composite Particles (Journal of Scientific Research, 2017)
Recently nano-sized conducting polymers have gained ample attention because of their unique properties and promising potentiality in nanomaterials and nanodevices. Among the conducting polymers, polyaniline (PANi) is the most studied conducting polymers because of its low monomer cost, ease of preparation, high conductivity in doped form, excellent environmental stability, controllable physical and electrochemical properties by oxidation and protonation. In this investigation magnetic PANi composite particles were prepared following a novel approach by using citric acid for the first time as dopant, surfactant and solubilizing agent. As synthesized citric acid doped Fe3O4 (magnetite)/PANi nanocomposites have been characterized by Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffractometer (XRD), Scanning electron microscope (SEM), Thermogravimetry analysis (TGA). Spectroscopic analyses confirmed the modification of Fe3O4 nanoparticles by PANi layer. The Magnetic susceptibility results revealed the paramagnetic behavior of Fe3O4/PANi nanocomposite particles. The electrical conductivities of Fe3O4/PANi nanocomposites increased up to certain amount of Fe3O4 and decreased thereafter.